Microbiological aspects of libraries’ safety - Surmasheva, O.V.; Rosada, M.O.; Omelchenko, M.M.; Nikonova, N.O.; Romanova, H.Yu.; Vulakh, N.O.; Oliinyk, Z.A. (Environment & Health, 2017)
Objective. We studied the problems of contamination of premises of the libraries and their funds with microorganisms, micromycetes in particular, to characterize epidemic safety of the premises, the information fund; to assess the epidemiological safety of the premises and libraries’ funds according to the data of microbiological examination; and to find safe and effective ways of combating with microbial contamination of the library environment.Materials and methods. Microbiological methods: determination of bacterial seeding of the air of libraries and swabs from surfaces of premises and carries of information with bacteria and microscopic fungi; identification of isolated microorganisms with the help of the common microbiological methods; model experiments for the study of the efficiency of salt lamps for air decontamination from microorganisms. Studies were performed in a number of large libraries of Ukraine.Results. Information on the reasons of the contamination of the premises and funds of the libraries with microscopic fungi, measures for prevention and elimination of biological pollution were analyzed. A necessity of the measures for the disinfection of the library funds and premises from pathogens of fungal and bacterial origin was proved. Fungal and bacterial contamination was shown to depend on the microclimatic conditions and the use of some measures of disinfection had a positive effect on the decontamination of premises and funds of the libraries. A high efficiency of the use of a salt lamp for the elimination of the microbial contamination of indoor air was proved in model experiments.Conclusions. Monitoring of the library environment is necessary for timely detection of microbiological (mycological) contamination, and there is a need in the effective methods of disinfection of premises and funds of the libraries. The high efficiency of salt lamp at air decontamination from bacteria and fungi was established.
Keywords: libraries; microbial contamination; bacteria; microscopic fungi; decontamination